2018
DOI: 10.1053/j.gastro.2018.05.038
|View full text |Cite
|
Sign up to set email alerts
|

World Endoscopy Organization Consensus Statements on Post-Colonoscopy and Post-Imaging Colorectal Cancer

Abstract: A 20-member international team has provided standardized methods for analysis of etiologies of PCCRCs and PICRCs and defines its use as a quality indicator. The team provides recommendations for clinicians, organizations, researchers, policy makers, and patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
302
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 264 publications
(315 citation statements)
references
References 72 publications
5
302
0
8
Order By: Relevance
“…Although the term “interval CRC” was loosely adopted by previous studies, majority of these studies failed to meet the definition as proposed: “CRC diagnosed after a screening or surveillance exam in which no cancer is detected, and before the date of next recommended exam.” In particular, “interval cancer” applies to screening and surveillance programs only and hence is not optimal for routine colonoscopy quality assurance purposes . In this study, we followed the recent World Endoscopy Organization (WEO) consensus on advocating the PCCRC rate for an interval of 3 years (PCCRC‐3y) for benchmarking purposes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the term “interval CRC” was loosely adopted by previous studies, majority of these studies failed to meet the definition as proposed: “CRC diagnosed after a screening or surveillance exam in which no cancer is detected, and before the date of next recommended exam.” In particular, “interval cancer” applies to screening and surveillance programs only and hence is not optimal for routine colonoscopy quality assurance purposes . In this study, we followed the recent World Endoscopy Organization (WEO) consensus on advocating the PCCRC rate for an interval of 3 years (PCCRC‐3y) for benchmarking purposes.…”
Section: Methodsmentioning
confidence: 99%
“…Chi‐squared test or Fisher's exact test was applied for categorical variables. The PCCRC‐3y rate was calculated as per WEO consensus: False negatives/(True positives + False negatives), where false negatives refer to colonoscopy with CRC subsequently diagnosed between 6 and 36 months after the procedure and true positives refer to colonoscopy with CRC diagnosed at or within 6 months of the procedure . Count data and temporal trends were assessed by Poisson regression model.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that if polypectomy was performed only during withdrawal, a significant number of polyps could be missed. Missing colon adenomas was associated with the development of post‐colonoscopy CRC . Thus, it is rational to resect small polyps when they are encountered during colonoscope insertion, and this could reduce the chance of being unable to locate the polyp on withdrawal.…”
Section: Discussionmentioning
confidence: 99%
“…Unit-level data are now available which provide PCCRC rates. PCCRC is potentially a single benchmark standard for units to assess the colonoscopy service they provide 29. Despite this being a JAG standard (units should record PCCRC as adverse events and have a mechanism to capture these data), at present it is unclear how most units manage this.…”
Section: Introductionmentioning
confidence: 99%